Administrative Organization and Its Role in Developing Professional Awareness among English Language Teachers - Julaid, Amal Sabbar (NIU Journal of Social Sciences, 2026)
This study aimed to identify the impact of administrative organization on developing professional awareness among English language teachers by examining the levels of both administrative organization and professional awareness, and analyzing the nature of the relationship between them. The study employed a descriptive correlational approach and included a sample of 200 male and female teachers from schools in Dhi Qar Governorate. Two questionnaires were used to measure both administrative organization and professional awareness, and their validity and reliability were verified using appropriate scientific methods. The results showed that the level of administrative organization was high, with a mean score of 174, which is higher than the hypothetical mean of 120, indicating a clear and organized organizational environment. The results also showed that the level of professional awareness among teachers was high as well, with a mean score of 164, reflecting a high level of understanding and commitment to the requirements of the profession. Furthermore, the results revealed a statistically significant positive correlation between administrative organization and professional awareness, indicating that improved administrative organization directly contributes to enhancing professional awareness among English language teachers. This finding underscores the importance of the organizational environment in shaping teachers' professional behavior and performance. The study recommends developing administrative systems within schools, strengthening professional development programs, and improving communication channels to raise professional awareness and enhance the quality of the educational process. Keywords: Administrative Organization, Professional Awareness, English Teachers.